Caracterização cariotípica de espécies de peixes do gênero Astyanax: uma contribuição para a análise da biodiversidade do grupo - Torres-Mariano, Alessandra Ribeiro (2010)
A cytogenetic study was conducted on an Astyanax eigenmanniorum population from the Caetano Stream (18° 44' 56" S/ 048° 18' 39" W) - in Uberlândia, MG, Brazil - showing a modal diploid number of 48 chromosomes in the standard male and female karyotypes. However, in several specimens it was also possible to observe metaphases with one or two B chromosomes, increasing the diploid number to 49 or 50 chromosomes, respectively. The supernumerary chromosomes were totally heterochromatic and highlighted after C-banding. The silver-stained nucleolus organizing regions (AgNORs) were located in at least five chromosomes of the standard karyotype, thus characterizing a multiple NOR system in the species. This is the first occurrence of an A. eigenmanniorum population with 2n = 48 chromosomes, bearing supernumerary chromosomes.